Assessing visitors' willingness to pay for mitigating recreational impacts on lakes ecosystems: a comparative study between Portugal and Nepal - Mário Almendra; Eduardo Pinheiro; Cláudia Costa; Márcio Martins (Millenium)
Introduction: The growing demand for recreational activities in natural areas often results in environmental degradation, jeopardising the sustainability of these ecosystems. Understanding visitors’ willingness to pay (WTP) to mitigate these impacts is crucial for supporting the sustainable management of these areas.